利用實驗小鼠模式探討血管收縮素轉化?(ACE2) 表現調節與肺纖維化有關之分子機轉 - 林志生; LIN CHIH SHENG (My University, 2013)
肺纖維化是一項慢性和複雜的疾病，可由多種原因導致，但大部分患者之病因不明，臨 床上稱之為原發性肺纖維化（idiopathic pulmonary fibrosis; IPF）。雖然在腎素-血管收縮素系 統中（renin-angiotensin system; RAS），已知血管收縮素轉化酶（angiotensin-converting enzyme; ACE）/ 血管收縮素II（angiotensin II; Ang II）途徑（ACE/Ang II axis）與許多肺部疾病有關， 但在RAS 系統中的另一個ACE 類似酵素，血管收縮素轉化酶II （angiotensin-converting enzyme II; ACE2）卻鮮少被探討，其在包括IPF 的一些肺部疾病中的病理生理機轉仍有許多未知。在 RAS 中，ACE2 可將Ang II 轉化成血管收縮素1-7（angiotensin 1-7; Ang-(1-7)），而Ang-(1-7) 被認為有拮抗Ang II 的生理功能。在我們過去的研究結果中顯示，ACE2/Ang-(1-7) axis 的異 常與心臟組織纖維化病程有關，而此可能經由基質金屬蛋白酶（matrix metalloproteinases; MMPs）與基質金屬蛋白酶組織抑制因子（tissue inhibitors of MMPs; TIMPs）的調控失衡有關。 在本計畫中，我們將探討肺部 ACE2 表現調節因子與肺纖維化病程有關之分子機轉，以 及MMPs/TIMPs 平衡調控與肺臟組織纖維化的關係。在本計畫中，我們針對上述的議題，擬 訂五個研究目標：(1) 瞭解肺臟組織中ACE2 表現之特定細胞，探討ACE2 基因表現的調節 因子，以及一些與肺纖維化病變有關之誘發因子（包括bleomycin、TGF-1、Ang II 及Ang-(1-7)） 對於肺組織中特定細胞的ACE2 表現之影響；(2) 建立肺纖維化實驗小鼠研究模式，利用ACE2 基因剔除（ACE2-/y）實驗小鼠與ACE2 活性控制，探討ACE2 在肺纖維化病程中扮演的角色； (3) 探討在肺纖維化病程中，MMPs 和TIMPs 的表現與活化態樣，並研究這些MMPs/TIMPs 的表現調節與ACE2 的相關性；(4) 探討特定MMPs/TIMPs 的活化劑（activator）和抑制劑 （inhibitor）對於進行中之肺纖維化病程的影響；(5) 篩選調節ACE2 表現可能存在之 microRNAs，印證此特定microRNAs 的表現與抑制是否影響肺纖維化之病程，為肺纖維化病 程控制帶來新藥物開發之契機。 由於目前 IPF 在臨床上尚無明確有效性的用藥，因此急需開發更有效率的治療藥物，而 我們的研究將有助於研究者更了解ACE2 表現調節與MMPs/TIMPs 的平衡調控在IPF 病程演 進中所扮演的角色，也提供IPF 在預防或治療上具開發潛能之新標的。

Pulmonary fibrosis is a chronic and complicated disease that can come from many different causes. In the majority of cases of this disease, the cause is not known, called idiopathic pulmonary fibrosis (IPF). Although angiotensin converting enzyme (ACE)/angiotensin II (Ang II) axis in renin-angiotensin system (RAS) has been recognized associated with the development of several pulmonary diseases, including IPF, much less is known about the function of angiotensin converting enzyme II (ACE2), an ACEhomologue that converts Ang II to angiotensin 1-7 (Ang-(1-7)), a peptide that exerts actions opposite to those of Ang II. In our previous studies, we showed that ACE2 dysregulation and unbalanced matrix metalloproteinases (MMPs)/tissue inhibitors of MMPs (MMPs/TIMPs) are highly associated with the fibrotic damage in cardiovascular diseases. In this project, we are ambitious to study the regulatory elements of ACE2 and molecular mechanism of ACE2 regulation on pulmonary fibrosis by experimental mouse model. We also attempt to study the roles of ACE2/Ang-(1-7) axis in pulmonary function and test the hypothesis that whether part of the anti-fibrotic effects of ACE2/Ang-(1-7) axis is via the balancing regulation of MMPs/TIMPs? In the present project, we propose five research goals addressing on the above subjects. (1) We will explore lung-selective ACE2 and the regulatory elements on ACE2 gene expression in pulmonary cells, fibroblasts and epithelium cells, treated with the fibrosis-induced factors, including bleomycin, TGF-1 and angiotensin peptides (Ang II and Ang-(1-7)). (2) The experimental mouse model of pulmonary fibrosis will be established. The pathophysiological roles of ACE2 in pulmonary fibrosis will be evaluated by ACE2 knockout (ACE2-/y) mice and via the administration of ACE2 activators or inhibitors. (3) The expression and activity profiles of MMPs and TIMPs in the developed pulmonary fibrosis will be assayed. We also attempt to understand the ACE2 regulation associated with the balanced expression and activity of MMPs/TIMPs. (4) The experimental mice administrated with MMPs/TIMPs activators or inhibitors will be performed to study the effects of unbalanced MMPs/TIMPs on the pathogenesis of pulmonary fibrosis. (5) We attempt to screen the microRNAs that can regulate ACE2 expression at translational level and investigate crucial roles of the ACE2 microRNAs in the fibrotic process of pulmonary fibrosis. The results can provide an opportunity of controlling ACE2-microRNAs expression in the therapy for pulmonary fibrosis. Our studies will be valuable in the understanding of anti-fibrotic effects of ACE2 expression. Difficulty in the clinical treatments for IPF represents an enormous clinical challenge in need of effective therapeutic approaches. The anticipated results of this project will provide new insight into the pathophysiological processes of IPF. Furthermore, our studies will also illustrate new potential targets or methods, by the modulation of ACE2 expression, ACE2/Ang-(1-7) axis and/or balanced MMPs/TIMPs control, for IPF prevention and treatments.
Studying the regulatory elements of angiotensin converting enzyme II (ACE2) and the molecular mechanism of ACE2 regulation on pulmonary fibrosis by experimental mouse models
Keywords: 肺纖維化; 血管收縮素轉化酶II; 基質金屬蛋白酶; 動物模式; Pulmonary fibrosis; Angiotensin converting enzyme II; Matrix metalloproteinases; Animal model